Thirdspace Perspectives on Student Marriage: Intersection of Culture, Space, and Identity in Bojonegoro, Indonesia - Cahyani, Ella Dwi; Susilo , Singgih; Abdulwahab , Bnar (CV Bumi Spasial, 2025)
Universities in Indonesia do not limit the age of prospective students who want to continue their education, so many married students continue their studies. The decision to get married while still studying will affect self-adjustment in dividing time between household duties and coursework. The concepts and definitions related to this research are based on the theories of Alfred Schutz, Mead and Blumer. Complementing these, Edward Soja's concept highlights how the subjects negotiate their identity within the intersection of academic (Firstspace) and domestic (Secondspace) environments. The approach used in this research is a phenomenological qualitative approach, so that researchers are directly involved and cannot be represented. The subjects used are actively married female students who are currently studying at Bojonegoro Regency Universities. Data collection procedures in the form of observation, in-depth interviews and literature studies. Data collection uses the source triangulation method which is analyzed according to Miles and Huberman. At the reduction stage, based on strict inclusion criteria verification, the research subjects were determined from 11 informants to 7 informants. The results of this study indicate that marriage in female college students is based on the concept of